The Economics Scholars Program: Creating a professional economics research conference for undergraduate students. Issue 1 (2nd January 2020) - Clayton, Stephen; Nuckols, Daniel
Abstract: Whether pursuing immediate professional careers or preparing for graduate research, for many students the opportunities to conduct original research as undergraduates can be formative, creating a valuable differentiating factor on their resumes. The Economics Scholars Program builds an environment where undergraduate students can conduct economic research and then follow with another facet of the research experience, namely, presenting at a professional conference. Due to a collaborative effort between Austin College and the Federal Reserve Bank of Dallas, the conference helps create research opportunities for undergraduates. The partnership enhances the Federal Reserve Bank of Dallas's commitment to thoughtful leadership in economics and building relationships. Entering its 14th year, the conference has grown from 23 participants in 2007 to over 300 participants from 36 schools in 2018.